2002
DOI: 10.1016/s0304-3959(02)00297-x
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity to superficial and deep stimuli in patients with chronic musculoskeletal pain

Abstract: In this study, we evaluated pain sensitivity in patients with fibromyalgia or other types of chronic, diffuse musculoskeletal pain to establish whether fibromyalgia represents the end of a continuum of dysfunction in the nociceptive system. One hundred and forty five patients and 22 healthy subjects (HS) completed an epidemiological questionnaire to provide information about fatigue, stiffness, sleep, the intensity of pain (VAS 0-100) and its extent both at onset and at present. Algometry was performed at all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
92
0
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(107 citation statements)
references
References 36 publications
6
92
0
9
Order By: Relevance
“…Increased pain sensitivity outside the areas of clinical pain has been reported for other regional pain syndromes, such as tension-type headache (50), temporomandibular disorder (51,52), and localized trapezius myalgia (18). Our findings are also consistent with those of other studies that have demonstrated lowered pain thresholds in patients with low back pain (53) and lowered thresholds in patients with regional or widespread pain who do not have the 11 tender points required for the diagnosis of fibromyalgia (54).…”
Section: Augmented Pain Processing In Idiopathic Chronic Low Back Painsupporting
confidence: 91%
“…Increased pain sensitivity outside the areas of clinical pain has been reported for other regional pain syndromes, such as tension-type headache (50), temporomandibular disorder (51,52), and localized trapezius myalgia (18). Our findings are also consistent with those of other studies that have demonstrated lowered pain thresholds in patients with low back pain (53) and lowered thresholds in patients with regional or widespread pain who do not have the 11 tender points required for the diagnosis of fibromyalgia (54).…”
Section: Augmented Pain Processing In Idiopathic Chronic Low Back Painsupporting
confidence: 91%
“…PPT and VAS are subjective clinical measurement tools and can only approximate of a true measurement of pain 21 . However, as both are assessing pain, it might be reasonable to expect that correlations would reach at least a value of 0.5 22 . Our findings for masseter muscle PPT/ VAS correlation were similar to List, Helkimo & Karlsson 16 .…”
Section: Discussionmentioning
confidence: 99%
“…3 Assuming that the main PFPS-related tissue pathologies are at the knee, the lower PPT in that region confirms localized hyperalgesia, which has been postulated as one of the underlying reasons for chronic pain conditions like PFPS. 4,14 The distal hyperalgesia observed at the tibialis anterior could reflect a loss of descending inhibitory processes. 16 Such impairment may lower the excitation threshold of spinal cord neurons to joint nociceptive input, increasing the receptive fields of neurons and ongoing discharges, and affect all segments along the neuroaxis.…”
Section: Discussionmentioning
confidence: 99%